2022
DOI: 10.1088/2053-1591/ac5cac
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laser power and scanning speed on forming structure in selective laser melting process

Abstract: With the continuous development of ship technology, the usage environment of some parts has changed, with higher requirements for materials and preparation technology being put forward. Some traditional structural materials have do not meet the actual working conditions of ships, which necessitates development of new materials and research on their preparation technology. Owing to its high strength and stable mechanical properties at high temperature, molybdenum base alloy is expected to replace nickel base al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…6 These issues are closely related to surface tension gradients, thermal capillarity, and bubble movement during the shaping process, ultimately significantly affecting the quality, performance, and safety of the formed parts. 7 Therefore, to optimize components performance, it is essential to exercise the precise control over some key parameters, such as laser power, scanning velocity, hatching spacing, and powder layer thickness. 8 Leung et al 9 found that with the increase in laser power, the wetting ability of the molten pool improves, as the scanning velocity increases, the continuous melting track change to interrupted hemi-cylindrical melting track and a series of independent molten beads forms.…”
Section: Introductionmentioning
confidence: 99%
“…6 These issues are closely related to surface tension gradients, thermal capillarity, and bubble movement during the shaping process, ultimately significantly affecting the quality, performance, and safety of the formed parts. 7 Therefore, to optimize components performance, it is essential to exercise the precise control over some key parameters, such as laser power, scanning velocity, hatching spacing, and powder layer thickness. 8 Leung et al 9 found that with the increase in laser power, the wetting ability of the molten pool improves, as the scanning velocity increases, the continuous melting track change to interrupted hemi-cylindrical melting track and a series of independent molten beads forms.…”
Section: Introductionmentioning
confidence: 99%
“…The application of different laser technologies also leads to different effects on the modified surface properties. Thus, for example, in addition to the power density and the energy density in the processing area, the scanning speed or the laser interaction time have a strong influence on the modification of a metal surface [10] [11] [12]. All these specific features determine the number of advantages of laser surface treatment over conventional treatment methods, such as local heating of the surface without changing the properties of the substrate material, precision, and high speed of work and low cost [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, lowering the flash intensity to mitigate this risk will reduce the sinter quality. Moreover, this method is not a direct patterning method, and an additional patterning process is required before and after Cu sintering.Another promising technique is direct laser sintering [22][23][24][25][26][27] . During focus, the focused beam energy is absorbed by the precursor and induces a localized, transient heating process that results in rapid sintering.…”
mentioning
confidence: 99%
“…Another promising technique is direct laser sintering [22][23][24][25][26][27] . During focus, the focused beam energy is absorbed by the precursor and induces a localized, transient heating process that results in rapid sintering.…”
mentioning
confidence: 99%